Collision of two communities: Developing higher education student teachers’ creativity in design through a social networking collaboration with professional designers - Abdullah, Zaleha (2011)
This study examines the activity of an online community in developing design creativity. This involved undergraduate Malaysian university students and their tutor from the School of Education, and professional designers in a private online community using the social network site - Facebook - to improve interface design (websites or interactive courseware). Two research processes adapted from different communities - the creative industries and the higher education communities - were applied in the collaboration. Each community embraces distinctive methods, objectives, instruments, rules and roles in producing design. Contradictions and tensions resulting from incorporating these two communities were analysed. In addition, the effect of social interactions on students’ performance, awareness, and perspectives were also investigated.